In Situ Solidification by γ−ray Irradiation Process for Integrated Solid−State Lithium Battery - Zhiqiang Chen; Xueying Yang; Nanbiao Pei; Ruiyang Li; Yuejin Zeng; Peng Zhang; Jinbao Zhao (Batteries, 2023)
The safety concerns associated with power batteries have prompted significant interest in all−solid−state lithium batteries (ASSBs). However, the advancement of ASSBs has been significantly impeded due to their unsatisfactory electrochemical performance, which is attributed to the challenging interface between the solid−state electrolyte and the electrodes. In this work, an in situ polymerized composite solid−state electrolyte (LLZTO−PVC) consisting of poly(vinylene carbonate) (PVC) and Li6.4La3Zr1.4Ta0.6O12 (LLZTO) was successfully prepared by a γ−ray irradiation technique. The novel technique successfully solved the problem of rigidity at the interface between the electrode and electrolyte. The LLZTO−PVC electrolyte exhibited a notable ionic conductivity of 1.2 × 10−4 S cm−1 25 °C, along with good mechanical strength and flexibility and an electrochemical window exceeding 4.65 V. It was showed that the LiCoO2(LCO)/LLZTO−PVC/Li battery, which achieved in situ solidification via γ−ray irradiation, can steadily work at a current density of 0.2 C at 25 °C and maintain a retention rate of 92.4% over 100 cycles. The good interfacial compatibility between electrodes and LLZTO−PVC electrolyte designed via in situ γ−ray irradiation polymerization could be attributed to its excellent electrochemical performance. Therefore, the method of in situ γ−ray irradiation polymerization provides a vital reference for solving the interface problem.